Ms. Interactive Learning Media Based on Educational Games to Improve the Reading Skills of First-Grade Elementary School Students - Gayatri, Ni Nyoman Elma Triana; I Made Suarjana; Putu Aditya Antara (Jurnal Pedagogi dan Pembelajaran, 2025)
Reading is a fundamental skill for first-grade students as the foundation of early literacy, cognitive development, and academic readiness; however, many elementary students are still unable to read or recognize the alphabet. The purpose of this study is to design learning media, examine the content validity of the media, and obtain an overview of practitioners’ and students’ responses to interactive learning media based on educational games. This research is a development study that refers to the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques included interviews, observations, and questionnaires. Data analysis was conducted quantitatively using validity index and achievement levels, as well as qualitatively through descriptive analysis of comments and suggestions from experts, practitioners, and students as the basis for media improvement. The results show that the interactive educational game-based reading media achieved a content validity index of 0.97, categorized as highly valid. Practitioners’ responses reached 96.5%, and students’ responses reached 97.7%, both categorized as excellent. This study demonstrates that the developed interactive game-based media can serve as an enjoyable and effective alternative solution for teaching reading at the elementary school level. The study implies that such media can be integrated into classroom practice as a pedagogical innovation to strengthen early literacy, enrich learning experiences, and enhance reading achievement among first-grade students.